A review of traditional and current methods used to potentially reduce toxicity of Aconitum roots in Traditional Chinese Medicine. (31st July 2017) - Liu, Shuai; Li, Fei; Li, Yan; Li, Weifei; Xu, Jinkai; Du, Hong
Abstract: Context: Aconitum species are well-known for their medicinal value and high lethal toxicity in many Asian countries, notably China, India and Japan. The tubers are only used after processing in Traditional Chinese Medicine (TCM). They can be used safely and effectively with the methods of decoction, rational compatibility, and correct processing based on traditional experiences and new technologies. However, high toxicological risks still remain due to improper preparation and usage in China and other countries. Therefore, there is a need to clarify the methods of processing and compatibility to ensure their effectiveness and minimize the potential risks. Object: The aim of this paper is to provide a review of traditional and current methods used to potentially reduce toxicity of Aconitum roots in TCM. Materials and methods: The use of Aconitum has been investigated and the methods of processing and compatibility throughout history, including recent research, have been reviewed. Results and conclusions: Using of the methods of rational preparation, reasonable compatibility, and proper processing based on traditional experiences and new technologies, can enable Aconitum to be used safely and effectively. Graphical abstract: